Mechanical, dielectric and microwave absorption properties of SiO2f/SiCf/PI composites. (19th September 2018) - Dong, Jie; Zhou, Wancheng; Jia, Hongyao; Chen, Qiang; Gao, Lu; Luo, Fa; Zhu, Dongmei; Lu, Linlin
Abstract: Structural radar absorbing material attracts increasing attention as an important part of microwave absorbing material. In this study, fiber cloths reinforced polyimide (PI) matrix composites consisting of different proportion of quartz glass fiber (SiO2f ) and silicon carbide fiber (SiCf ) cloth were designed and prepared by adjusting the proportion. The morphology, mechanical, dielectric properties and electrical conductivity of the composites were thoroughly studied in X band (8.2–12.4 GHz). The results showed that the position of SiCf cloth in the composite had little effect on the dielectric properties of the composite. Under the action of load, the fracture of composites containing different contents of SiCf cloth showed different fracture modes. As the content of SiCf cloth increased in the composite material, both the real and imaginary parts of complex permittivity showed an increasing trend. The electrical conductivity of the composites also increased gradually with content of SiCf cloth rise. The reflectivity of the composites was calculated according to transmission line theory. Variation of fiber cloth composition in this study offered a new strategy to simultaneously improve the mechanical and microwave absorbing properties of PI-based structural absorbing materials.